Agentura wpływu uczestnikiem walki informacyjnej - Żebrowski, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The secret service and manipulation are connected. This is relevant to state security and defense. The intelligence and counterintelligence services play a pioneering role in these sectors of functioning. Each of them affects the opponent in terms of their activities. This influence requires knowledge, skills and the participation of agentry – which performs many complex tasks to distort the enemy’s information – in addition to other staff resources. Especially important is the impact agentry because of its capabilities. It is in an operational interest environment and is a participant in the decision-making process related to the state security.
Keywords: wojna informacyjna; źródła danych osobowych; zniekształcenie informacji